Fabry disease: Treatment and diagnosis - Rozenfeld, Paula (2009)
Fabry disease is an X-linked lysosomal disorder that results from a deficiency of the lysosomal enzyme α-galactosidase A leading to accumulation of glycolipids, mainly globotriaosylceramide in the cells from different tissues. Classical Fabry disease affects various organs. Clinical manifestations start at early age and include angiokeratoma, acroparesthesia, hypohydrosis, heat/exercise intolerance, gastrointestinal pain, diarrhea, and fever. The main complications of Fabry disease are more prominent after the age of 30 when kidney, heart, and/or cerebrovascular disorders appear. Most of the heterozygous females are symptomatic. Enzyme replacement therapy (ERT) is the only specific treatment for Fabry disease. The beneficial effect of ERT on different organs/systems has been extensively evaluated. Quality of life of patients receiving ERT is improved. Enzyme replacement stabilizes or slows the decline in renal function and reduces left ventricular hypertrophy. Fabry disease may be underdiagnosed because of nonspecific and multiorgan symptoms. Different screening strategies have been carried out in different at-risk populations in order to detect undiagnosed Fabry patients. An increasing knowledge about Fabry disease within the medical community increases the chances of patients to receive a timely diagnosis and, consequently, to access the appropriate therapy.